Caste Politics: Klientelisme dalam Pemerintahan Ram Nath Kovind terhadap Kasta Dalit di India - Meliana, Ni Luh Ayu; Erawan, I Ketut Putra; Pramana, Gede Indra (Jurnal Nawala Politika, 2023)
This research will explain the political discrimination against the Dalit caste as the lowest caste in India. Caste hierarchy and its role in politics and access to power and resources have created a society that has patron-client relationships along caste lines. The method used in this research is qualitative with a more specific domain in India during the reign of Ram Nath Kovind (2017-2022). Research utilizes the theory of clientelism and subaltern to explain that it is part of ‘politics of survival’ in an insecure political environment. Studies related to clientelism are important considering that historical and structural perspectives regarding caste exploitation in India have influenced the phenomenon of relations and patterns of power in politics in developing countries. The findings in this research found that conflicts of interest triggered the waning of Ram Nath Kovind's loyalty to the Dalit caste. It is clear that political clientelism towards the Dalit caste only benefits patrons without a win-win solution.